Action! - Keene, Carolyn; Copyright Paperback Collection (Library of Congress) (New York : Aladdin Paperbacks, 2004)
Nancy has a part in a film reenactment of the heist that gave her town its name. When the cameras start rolling trouble begins.
Keywords: Drew, Nancy (Fictitious character); Drew, Nancy (Fictitious character); Detective and mystery stories